Developing social responsibility among students of the Zubeir High School for Excellence In light of the requirements of sustainable development - Najm, Dr. Saad Akkamush (Thi Qar Arts Journal, 2023)
Developing social responsibility among students of the Zubeir High School for Excellence In light of the requirements of sustainable development Dr. Saad Akkamush Najm Education of Basra Governorate - Zubair Education Department Abstract: The current study aimed to present a proposed concept for developing social responsibility among students of the Zubeir High School for Excellence in light of the requirements of sustainable development, and the descriptive approach was used, and the researcher prepared a questionnaire form to measure the reality of social responsibility among high school students in the city of Zubair, and the number of questionnaire questions reached (51) questions distributed over five axes: (personal responsibility, collective responsibility, ethical responsibility, economic responsibility, environmental responsibility), and through the questions posed, the level of feeling of social responsibility and sustainable development among the sample units was identified, and the individual differences of the sample axes under study were identified, where the data were collected for the sample by distributing the questionnaire form to the students of the Zubeir High School for Excellence by (183) forms, (181) forms were accepted while (2) forms were excluded due to errors in them. The data were processed using the statistical package for social sciences (spss), and some of the research results were as follows:• The sample units of the research enjoy a good degree of social responsibility.• There are no differences in the level of feeling of responsibility among high school students according to the variable of stage, age, social status or place of residence.• The sample units of the research from the students bear social responsibility according to the dimensions of sustainable development.• The results showed direct and indirect effects between social responsibility and the dimensions of sustainable development.